Personalized Learning Paths in Open Education Systems - Abaa, Angela Ebere (NIU Journal of Educational Research, 2025)
The concept of education reflected in open education systems and their personalized learning paths is future-changing. Here, learners meet their personalized learning content according to their needs, interests, and learning speed. The idea is supported by technology, using adaptive learning platforms, data analytics, and open education resources, to make experiences flexible, learner-centred, and enhance access and engagement. The potential for personalized learning pathways is huge in open education systems, which should provide quality and low-cost education to very diverse populations. However, successful personalized learning faces challenges on infrastructure, data privacy, quality of content, and digital literacy. The personalized learning paths in open education can further allow for improved learning outcomes, scalability, and increased learner autonomy by tackling a number of challenges in the presentation of recommendations for their effective implementation. Personalized learning paths-aided by adaptive technologies and collaborative learning strategies-support more inclusive, flexible, and equitable education systems, especially in areas where access to traditional education systems is at a minimum. Keywords: Personalized learning paths, open education systems, adaptive learning, data analytics, educational technology, scalability, digital literacy